2013
DOI: 10.1167/13.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Pupil size signals novelty and predicts later retrieval success for declarative memories of natural scenes

Abstract: Declarative memories of personal experiences are a key factor in defining oneself as an individual, which becomes particularly evident when this capability is impaired. Assessing the physiological mechanisms of human declarative memory is typically restricted to patients with specific lesions and requires invasive brain access or functional imaging. We investigated whether the pupil, an accessible physiological measure, can be utilized to probe memories for complex natural visual scenes. During memory encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
139
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(160 citation statements)
references
References 90 publications
14
139
7
Order By: Relevance
“…More recent studies have linked pupil dilation to surprise about behaviorally relevant events (10,12,54), perceptual target detection (11,13), and report of transitions between percepts in bistable perceptual phenomena (6,14). Taken together, these findings establish that pupil dilation is a faithful reporter of the mental state of decision makers.…”
Section: Discussionmentioning
confidence: 79%
“…More recent studies have linked pupil dilation to surprise about behaviorally relevant events (10,12,54), perceptual target detection (11,13), and report of transitions between percepts in bistable perceptual phenomena (6,14). Taken together, these findings establish that pupil dilation is a faithful reporter of the mental state of decision makers.…”
Section: Discussionmentioning
confidence: 79%
“…However, recently a growing body of evidence has shown that the pupil not only constricts to physically bright object, but also to bright illusions (Laeng and Endestad, 2012), and even to imaginary bright situations (Laeng and Sulutvedt, 2014). Moreover, pupil constrictions as well respond to a variety of visual attributes besides brightness, including the inversion effect (Conway et al, 2008; Naber and Nakayama, 2013), novelty (Naber et al, 2013), conspecific faces (Conway et al, 2008; Ebitz et al, 2014), threatening animals (Naber et al, 2012), and the sun (Binda et al, 2013; Naber and Nakayama, 2013). The current study extends the scope of stimulus properties the pupil responds to, and demonstrates that it also constricts to subliminal threatening content conveyed by impending collision.…”
Section: Discussionmentioning
confidence: 99%
“…This sample size was fixed with reference to prior pupillometry studies involving recognition memory (e.g. Naber et al, 2013;Otero et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The pupil is also sensitive to episodic memory judgments, dilating more for recognition probes identified as studied (old) versus unstudied (new) (Gardner, Mo, & Borrego, 1974;Heaver & Hutton, 2011;Naber, Frassle, Rutishauser, & Einhauser, 2013;Papesh, Goldinger, & Hout, 2012;Vo et al, 2008). As an extension of earlier work linking pupillary dilation to cognition (Beatty, 1982;Kahneman, 1973), this 'pupil old/new effect' has been suggested to reflect the increased 'cognitive load' or voluntary effort required during the successful retrieval of episodic content.…”
Section: Introductionmentioning
confidence: 99%